Ernest Dichter and motivation research: new perspectives on the making of post-war consumer culture ; [papers and discussions at the First International Conference on Ernest Dichter and Motivation Research, organised by the editors at the University of Vienna in December 2005] - Schwarzkopf, Stefan; Gries, Rainer; Dichter, Ernest (Palgrave Macmillan, 2010)
"Contextualizing Ernest Dichter within modern consumer culture and the rise of psychological approaches to post-war consumption in Europe and the US, this book argues that 1950s motivation research gives a unique vantage point from which to address questions of the transatlantic transfer of the cultures and institutions of consumption and marketing"--